Dictatorships and the Return of Exiles. Chile and Argentina in a Comparative Perspective (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The military dictatorships of Chile (1973-1990) and Argentina (1976-1983) resulted in a large number of exiles. Likewise, the return of these exiles caught the attention of each dictatorship differently. By a comparative approach, the present article analyzes the military dictatorships’ answers to the exiles’ homecoming. Departing from the comparison, this article posits that exiles’ returns were state resources and political strategies to channel internal and external conflicts that were circulating the authoritarian regimes in the region.
Keywords: Political Exiles; Military Dictatorships; Comparative History; Chile; Argentina.